Salmonella A Re-emerging Pathogen - Teresa Mascellino, Maria (IntechOpen, 2018)
This book deals with the microorganism Salmonella. This bacterium is well known for a long time, being involved in systemic (typhus and paratyphus infections) and nonsystemic diseases such as food poisoning. Major and minor Salmonellae are widespread worldwide in developing countries and industrialized areas, respectively. In 2015, about 3576 Salmonella strains have been isolated from human infections in Italy. S. typhimurium and S. enteritidis are the most prevalent serotypes and represent 80% of cases of infections over the last 10 years. The antibiotic susceptibility decrease over the last decades is a big issue in the management of this bacterium, once considered easy to treat. The use of antibiotic combinations in order to overcome the microorganism resistance should be hoped.